USE FOLK PEDAGOGICAL METHODS TO EDUCATE YOUNG PEOPLE IN A SPIRIT OF NATIONAL GROWTH FROM NATIONAL RECONSTRUCTION (American Journal of Pedagogical and Educational Research, 2023)
Family and school cooperation plays a major role in the formation of young people, children, and children who are the future of our country as independent and free individuals, as well as the use of folk pedagogical methods to educate an active citizen in all aspects of education.